The oldest and first nearly complete skeleton of a chelid, of the Hydromedusa sub-group (Chelidae, Pleurodira), from the Upper Cretaceous of Patagonia - Fuente, Marcelo Saúl de la (2001)
A new pleurodiran (side necked) turtle is described on material from the Upper Cretaceous of Patagonia, from sediments outcropping at Cerro Blanco, Yaminue Creek, Rio Negro, Argentina. The sediments are compared to those from the Pellegrini lake area referred to the middle Member of the Allen Formation, Upper Campanian-Lower Maastrichtian. Yaminuechelys gasparinii n.g., n.sp., is a pleurodiran turtle on the pelvis sutured to the shell and a chelid on the formula of cervical vertebrae and the lateral cheek emargination, deeply extended towards (as here) or up to the posterior emargination. It is the oldest record of a nearly complete skeleton of a chelid, long necked (elongated cervical vertebrae, lowered skull), and the first sufficiently known of the Chelodina-Hydromedusa group (elongated skull, lowered neural arch and centrum of the cervicals, low zygapophyses processes, strong polygoned decoration) and of the Hydromedusa sub-group (widened inner nares by reduced palatine ossification). The carapace is 41,8 cm long. It is more primitive than Hydromedusa (Eocene-Extant, South America) and retains primitive characters either still present or no more present in the other chelids of the Pseudemydura, Emydura and Phrynops groups (short necked) and Chelus group (long necked), representing the anterior clades of phyletic diversification [Gaffney, 1977], or evolutive grades, of the family. Such are plesiomorphic, relative to Hydromedusa, the less pronounced lateral skull emargination, wider and longer hyoid elements, wider nucal and cervical, this not drawn back, presence of lateral mesoplastra, not shortened bridge, straight borders of the not shortened and not widened posterior plastral lobe, amphicoelous sacrals and caudal vertebrae uniting amphicoelous, concavoplaty--(i.e. anteriorly concave, posteriorly flat) and procoelous or weakly procoelous elements. As Hydromedusa, Yaminuechelys n. g. retains primitive characters such as the long series of neurals, the very lateral attachment of the axillar and inguinal processes and the attachment of the pelvis, below pleural 8 (and 7 in the extant form) and a small part of the suprapygal, and the ischitatic sutures prolonged on the xiphiplastral points. It is distinguished by the apomorphic presence of a wide and week anterior carapacial notch. Yaminuechelys n.g., or aff. Yaminuechelys spp. are known in Patagonia by fragmentary remains in a dozen of Upper Cretaceous and two Palaeocene localities. Before them, chelids are known in the world only by undefined smaller forms from Lower Albian and Upper Albian-Cenomanian Patagonian localities. In Australia, they are known from Palaeocene-Lower Eocene (no Cretaceous data before) with already extant Australian diversified forms. Yaminuechelys n.g. demonstrates how long the diversification in chelids is realized in South Gondwana before the full break of the continents.